Variabilidade sazonal e controle biofísico da evapotranspiração na vegetação do bioma Pampa - Rubert, Gisele Cristina Dotto (2017)
Evapotranspiration (ET) is an important component that connects water and energy cycles in terrestrial ecosystems. Understanding how ET changes with environmental factors is critical to a better understanding of ecological and hydrological processes. Likewise, surface conductance (Cs) and aerodynamic conductance (Ca) are considered complex and determinant variables in most land surface models. In this study, data from two sites were used in the Pampa biome, Santa Maria and Pedras Altas, distant about 300 km. The data analyzed are atmospheric measurements of the environmental variables and surface fluxes, obtained from the eddy covariance method, over a period of two years, concomitant at both sites. The objective of this work was to evaluate the energy balance, the biophysical control of the evapotranspiration by the estimation of surface and aerodynamic conductances and the seasonal variability of the real evapotranspiration of the Pampa biome. During the study period, approximately 60% of the available energy was used for the evapotranspiration process on the Pampa biome. During the seasons of the year, separated by autumn-winter (OI) and spring-summer (PV) periods, latent heat flux was the main energy balance component in both periods. The Pampa biome presents a strong seasonality of evapotranspiration, with the highest evapotranspiration rates in the PV period. Finally, hysteresis curves for ET and Cs were observed in relation to environmental variables, radiation balance, vapor pressure deficit and air temperature. Among the variables analyzed, in the Pampa biome, surface conductance and evapotranspiration responded more strongly to the vapor pressure deficit. And, the hysteresis cycles formed by ET and the conductances showed strong biophysical control in the ET process complex.